Surface Functionalized MXenes for Wastewater Treatment—A Comprehensive Review. Issue 6 (20th March 2022) - Damptey, Lois; Jaato, Bright N.; Ribeiro, Camila Silva; Varagnolo, Silvia; Power, Nicholas P.; Selvaraj, Vimalnath; Dodoo‐Arhin, David; Kumar, R. Vasant; Sreenilayam, Sithara Pavithran; Brabazon, Dermot; Kumar Thakur, Vijay; Krishnamurthy, Satheesh
Abstract: Over 80% of wastewater worldwide is released into the environment without proper treatment. Whilst environmental pollution continues to intensify due to the increase in the number of polluting industries, conventional techniques employed to clean the environment are poorly effective and are expensive. MXenes are a new class of 2D materials that have received a lot of attention for an extensive range of applications due to their tuneable interlayer spacing and tailorable surface chemistry. Several MXene‐based nanomaterials with remarkable properties have been proposed, synthesized, and used in environmental remediation applications. In this work, a comprehensive review of the state‐of‐the‐art research progress on the promising potential of surface functionalized MXenes as photocatalysts, adsorbents, and membranes for wastewater treatment is presented. The sources, composition, and effects of wastewater on human health and the environment are displayed. Furthermore, the synthesis, surface functionalization, and characterization techniques of merit used in the study of MXenes are discussed, detailing the effects of a range of factors (e.g., PH, temperature, precursor, etc.) on the synthesis, surface functionalization, and performance of the resulting MXenes. Finally, the limits of MXenes and MXene‐based materials as well as their potential future research directions, especially for wastewater treatment applications are highlighted. Abstract : 2D nanomaterials, especially MXenes have recently seen exciting developments in research and development, and their application in wastewater treatment has drawn wider attention. This review examines state‐of‐the‐art strategies employed in synthesis, functionalization, and characterization of surface functionalized MXenes. Furthermore, engineering strategies like composition design, and how surface protection influence their properties as adsorbents, photocatalysts, and membranes in wastewater treatment are discussed.